2009
DOI: 10.1007/s10522-009-9232-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carnosine treatment on prooxidant–antioxidant balance in liver, heart and brain tissues of male aged rats

Abstract: Carnosine (beta-alanyl-L: -histidine) is a dipeptide with antioxidant properties. Oxidative damage by free radicals is one of the mechanisms underlying the aging process. This study was done to investigate the effects of carnosine treatment on lipid peroxidation and antioxidant status of liver, heart, brain in male young and aged rats. At the initiation of study, young and aged rats were 5 and 22 months old, respectively. Carnosine (250 mg/kg, daily, i.p.) was administered for 1 month to rats. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…Several reports show that supplementation with other exogenous antioxidants, e.g. melatonin and carnosine, could eradicate the harmful effects of FA [2,47]. The total oxidant capacity increased with FA exposure in a dose-dependent way (low to high dose FA) in our study.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Several reports show that supplementation with other exogenous antioxidants, e.g. melatonin and carnosine, could eradicate the harmful effects of FA [2,47]. The total oxidant capacity increased with FA exposure in a dose-dependent way (low to high dose FA) in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have reported decreased antioxidant capacity after FA exposure [6,19,20,39,[47][48][49]. We maintain that the decrease in antioxidant capacity associated with FA inhalation results from changes in the activities of antioxidant enzymes, such as glutathione reductase (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase [6, 19, 20, 39, , 47-49], as well as carnosine supplementation [2]. Carnosine and these enzymes adjust their activities to Page 13 of 29 A c c e p t e d M a n u s c r i p t 13 protect cells against oxidative damage [2,8].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The fact that supplementation of carnosine in nonruminants was able to rescue prooxidant-antioxidant balance by restoring depleted levels of blood GSH and activities of antioxidant enzymes (Aydin et al, 2010) indicates the potential decrease in circulating carnosine in events of oxidative stress. Although the contribution of carnosine to restore prooxidant-antioxidant balance under physiologic (without carnosine supplementation) conditions remains unknown, the overall greater circulating carnosine together with greater circulating taurine as well as hepatic GSH reported previously (Zhou et al, 2016a) indicate a less pronounced oxidative stress status in response to periparturient MET supplementation.…”
Section: Aa Derivativesmentioning
confidence: 99%